Extraction of psychological problems of female athletes - Zippo, K.; Okuno, M.; Katagami, E.; Kondo, M.; Shimizu, S.; Tsuchiya, H. (Journal of High Performance Sport, 2019)
Psychological problems faced by women athletes were investigated from various perspectives, including the menstrual dysfunction and sports environment to develop a psychological support program for female athletes. A questionnaire was administered to women athletes (N=147). The participants were classified into two groups to compare performance: athletes with participation in inter-national athletic events (N=67) and those with participation in national athletic meetings (N=80). Participants were asked to respond about the conditions and incidents they had experienced during the last two or three months using a five-point scale ranging between 1 (Not at all) to 5 (Very often). They were also requested to freely describe their current physical and psychological difficulties and prob-lems, as well as interpersonal relationships, among others. The results of free description were categorized using the KJ method. Results indicated that female athletes participation in international athletic events had problems related to the environment, such as the small size of practice fields and the insufficient number of female staff members. On the other hand, those with participating in national athletic meetings complained of the decline in concentration because of period pain, among others. It is suggested that athletes with participation in international athletic events might maintain their concentration without being affected by physiological conditions. Moreover, clear differences in problems characteristic to female athletes such as period pain were indicated based on the athletes` performance levels, which should be taken into consideration in developing a psychological support program for elite female athletes.